2007
DOI: 10.1073/pnas.0605527104
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of metal-independent decomposition of organic hydroperoxides and formation of alkoxyl radicals by halogenated quinones

Abstract: The metal-independent decomposition of organic hydroperoxides and the formation of organic alkoxyl radicals in the absence or presence of halogenated quinones were studied with electron spin resonance (ESR) and the spin-trapping agent 5,5-dimethyl-1-pyrroline N-oxide (DMPO). We found that 2,5-dichloro-1,4-benzoquinone (DCBQ) markedly enhanced the decomposition of tert-butylhydroperoxide (t-BuOOH), leading to the formation of the DMPO adducts with t-butoxyl radicals (t-BuO • ) and methyl radicals ( • CH3). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
81
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 16 publications
4
81
0
1
Order By: Relevance
“…4 We have recently shown that halogenated quinones could enhance the decomposition of hydroperoxides and formation of alkoxyl/hydroxyl radicals independent of transition metal ions. [5][6][7][8] A new carbon-centered quinone ketoxy radical ( CBQ-OH, MW: 157) adduct with the spin-trapping agent DMPO (5,5-dimethyl-1-pyrroline N-oxide) (simply referred to here as DMPO-157) was observed during the reaction between 2,5-dichloro-1,4-benzoquinone (DCBQ) and t-butylhydroperoxide (t-BuOOH). 7 However, although we can observe the ESR signal for DMPO-157, we cannot directly detect its nitroxide radical form, but only its corresponding more stable non-radical nitrone form, by mass spectrometry (MS).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 We have recently shown that halogenated quinones could enhance the decomposition of hydroperoxides and formation of alkoxyl/hydroxyl radicals independent of transition metal ions. [5][6][7][8] A new carbon-centered quinone ketoxy radical ( CBQ-OH, MW: 157) adduct with the spin-trapping agent DMPO (5,5-dimethyl-1-pyrroline N-oxide) (simply referred to here as DMPO-157) was observed during the reaction between 2,5-dichloro-1,4-benzoquinone (DCBQ) and t-butylhydroperoxide (t-BuOOH). 7 However, although we can observe the ESR signal for DMPO-157, we cannot directly detect its nitroxide radical form, but only its corresponding more stable non-radical nitrone form, by mass spectrometry (MS).…”
mentioning
confidence: 99%
“…[5][6][7][8] This work was supported by NSFC Grants (21237005, 20925724, 21077058 and 21107139) and NIH Grants (ES11497, RR01008 and ES00210) (B.Z.). The authors also acknowledge the technical help provided by Dr H. T. Zhao.…”
mentioning
confidence: 99%
“…And during the autoxidation of TCHQ to TCBQ, the producing O 2 •− radical could be changed into H 2 O 2 , and producing OH . radicals from the reaction of H 2 O 2 and TCBQ could do damage to DNAs as demonstrated by Zhu et al [8,[22][23][24]. Therefore, we also examined the induction of oxidative DNA damage by H 2 O 2 and TCBQ, a metabolite of the TCHQ autoxidation reaction.…”
Section: Genotoxicity Of Tchq and The Evaluation Of Cellular Repair Omentioning
confidence: 91%
“…However, when DNA was administered along with H 2 O 2 and TCBQ, differences in the DNA strand breakage became significant when compared with the control. Mechanisms by which hydroxyl radicals are produced from TCBQ/H 2 O 2 have been verified as a metal-independent molecular mechanism [22,23]. During this reaction, TCBQ not TCSQ radical is essential to produce OH .…”
Section: Genotoxicity Of Tchq and The Evaluation Of Cellular Repair Omentioning
confidence: 95%
“…22 It is worth noting that a small radical signal was also detected in both DCBQ and 2,6-dichloro-1,4-benzoquinone (2,6-DCBQ) systems but could not be observed in Fe and other XQ systems (for further identification of this radical adduct, see section 3 below). In contrast, incubation of either compound alone did not lead to t-BuO • or • CH 3 generation (Figure 3).…”
Section: Metal-independent Rooh Decompositionmentioning
confidence: 99%